2018
DOI: 10.1007/s00404-018-4824-3
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoproteins (HDL) composition and function in preeclampsia

Abstract: HDL from women with PE reduced PON1 activity and increased ApoA1 release from HDL particles. This process was associated with increased HDL diameter, suggesting impaired HDL anti-oxidant activity. These changes might contribute to higher long-term cardiovascular risks among women with PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…Thus, practical laboratory markers which can help in assessing the onset and severity of PE remain to be studied. In recent years, an increasing number of studies are giving attentions to the correlation between serum markers and severity of PE [30][31][32]. Soluble endoglin and soluble fms-like tyrosine kinase-1 [16], serum ceruloplasmin [21], and soluble LIGHT [22] in the early phrase of pregnancy are often reported to have possible value in PE prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, practical laboratory markers which can help in assessing the onset and severity of PE remain to be studied. In recent years, an increasing number of studies are giving attentions to the correlation between serum markers and severity of PE [30][31][32]. Soluble endoglin and soluble fms-like tyrosine kinase-1 [16], serum ceruloplasmin [21], and soluble LIGHT [22] in the early phrase of pregnancy are often reported to have possible value in PE prediction.…”
Section: Discussionmentioning
confidence: 99%
“…PON1 is associated with a specific HDL subspecies and has a major role in the antioxidative activity of HDL [12]. In a recent study [8], we demonstrated that HDL from women with pre-eclampsia have decreased PON1 activity and increased APOA1 release. In the present study, we found similar patterns in APOA1 released from GDMA2-HDL.…”
Section: Discussionmentioning
confidence: 71%
“…PON1 is associated with a specific HDL subspecies and has a major role in the antioxidative activity of HDL [12]. In a recent study [8], we demonstrated that HDL from women with pre-…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies have suggested that apolipoproteins can participate in carcinogenesis by promoting proliferation and invasion, enhanced antitumor immunity or drug delivery, and an immediate oxidative stress reaction [11][12][13][14][15][16]. Apolipoprotein A-I (ApoA-I), mainly synthesized in the liver and the small intestine, is a major fraction of HDL-C, accounting for approximately 70% [17,18]. In CRC patients, the serum ApoA-I level has been reported to be an independent prognostic indicator to predict chemotherapy efficacy and survival time [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%